Entrepreneurial management - Acierto, Marife Agustin; Gordonas, Annabelle (Intramuros, Manila, Philippines : Unlimited Books Library Services and Publishing Inc., 2019)
This book is envisioned by the author as a reference material for students taking courses in Business Opportunities as introduction to the development of entrepreneurship.
CHAPTER 1. Concept of entrepreneurship -- 2. Economic developments of entrepreneurship -- 3. Developing a business plan -- 4. Identification of target market -- 5. Branding strategies -- 6. Marketing mix in the development of marketing strategy -- 7. Management requirements -- 8. Finance: Analyzing financial statements and creating projections -- 9. Business operations and implementations -- Bibliography
Includes bibliographical references.
Keywords: ENTREPRENEURSHIP